(1,2) *-D*-closed sets and (1,2) *-D**-closed sets in ideal bitopological spaces - Asokan, Dr. R.; P., Deviprabha. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this paper, we introduce the notion of (1,2)*-D*-closed sets and (1,2)*-D**-closed sets in ideal bitopological spaces. Additionally, we examine the characteristics of the novel concepts and contrast them with preexisting ones.